Internalizing Islamic leadership values through a deep learning approach in Islamic education - Atika Nailah Syirva; Anggellita Salsabila Prasidha; Asfida Rahma; Kania Afra Afifah; Zaenab Niswati Kamali; Mamluaturrohmah Mamluaturrohmah (ATTARBIYAH: Journal of Islamic Culture and Education, 2026)
This article examines the internalization of Islamic leadership values through a deep learning approach in Islamic Religious Education (IRE) classes at SMPN 1 Pace Nganjuk. Based on the assumption that IRE plays a strategic role not only in transmitting religious knowledge but also in shaping students' character and leadership attitudes, this study employs a qualitative descriptive method with a case study design. Data were collected through classroom observations, in-depth interviews with teachers and students, and document analysis, then analyzed using data reduction, presentation, and conclusion-drawing techniques supported by triangulation. The findings show that the deep learning approach promotes meaningful learning by encouraging critical thinking, reflection, and contextual understanding of Islamic leadership values such as responsibility, honesty, justice, cooperation, and exemplary behavior. Through problem-based learning, reflective discussions, and collaborative activities, students internalize these values cognitively, affectively, and behaviorally. The study concludes that deep learning transforms Islamic Education from a knowledge-oriented approach into a value- and character-oriented learning process, making it an effective strategy for strengthening students' Islamic leadership character.